2018
DOI: 10.1139/cjfas-2016-0340
|View full text |Cite
|
Sign up to set email alerts
|

The influence of discharge, current speed, and development on the downstream dispersal of larval nase (Chondrostoma nasus) in the River Danube

Abstract: Abstract:We investigated the mode (active versus passive) of larval downstream dispersal and its influencing factors in the nase carp (Chondrostoma nasus). Marked larvae (early and later stages), together with equivalent numbers of passive particles, were released in the main channel of the River Danube (Austria) at different flow (low, high) and current (over-critical, under-critical) conditions. Larvae and particles were recaptured with stationary nets at varying distances from release. We assumed that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 77 publications
0
32
1
Order By: Relevance
“…The contradiction with our results is presumably related to differences in the ecology of fish larvae (our results are mainly based on clupeids, while Lechner et al (2017) used nase) and scale of observations. Drifting larval nase had been sampled in the shallow- water inshore zone (Lechner et al 2017) and clupeids across the Volga River (Pavlov et al 1995).…”
Section: Habitat Scaling and Dsm: Distribution And Behaviour Of Migracontrasting
confidence: 98%
See 2 more Smart Citations
“…The contradiction with our results is presumably related to differences in the ecology of fish larvae (our results are mainly based on clupeids, while Lechner et al (2017) used nase) and scale of observations. Drifting larval nase had been sampled in the shallow- water inshore zone (Lechner et al 2017) and clupeids across the Volga River (Pavlov et al 1995).…”
Section: Habitat Scaling and Dsm: Distribution And Behaviour Of Migracontrasting
confidence: 98%
“…This suggests that hydrophysical processes play a primary role in DSM at this scale. However, in situ observations of the spatial distribution of drifting larval nase (Chondrostoma nasus) have shown that larvae disperse unlike passive particles (Lechner et al 2017). The contradiction with our results is presumably related to differences in the ecology of fish larvae (our results are mainly based on clupeids, while Lechner et al (2017) used nase) and scale of observations.…”
Section: Habitat Scaling and Dsm: Distribution And Behaviour Of Migramentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersal modes of fish during the crucial larval phase of their life cycle is an important factor in recruitment and is governed by abiotic triggers (e.g., hydrology and hydraulics: Pavlov (1994); and discharge: Lechner et al 2017;Korman et al (2004); Reichard and Jurajda (2004)), in combination with biotic triggers (e.g., physiology and behaviour: Gaudin and Sempeski (2001); Heggenes and Dokk (2001);Pavlov (1994)). In a study on juvenile fish movement, Pavlov et al (2008) concluded that micro-scale habitat heterogeneity, interacting with individual behavioural variability within fish populations, could affect the proportion of resident to migratory fish in a river.…”
Section: Introductionmentioning
confidence: 99%
“…The movement patterns observed in this study (Glas et al 2017), which, when coupled with a 3D hydrodynamic model, enable prediction of the effects of discharge, bed morphology, as well as restoration measures on the distribution patterns of the early stages of fish in rivers. Lechner et al (2018) show in their field experiment that the drift mode and spatial drift patterns of marked and recaptured larvae differ substantially from simultaneously released, passively drifting plastic particles. In this environment, the interrelationship of discharge and inshore morphology are relevant factors that influence the dispersal of the early stages.…”
mentioning
confidence: 99%